A new Ediacaran fossil with a novel sediment displacive life habit. (January 2014) - Droser, Mary L.; Gehling, James G.; Dzaugis, Mary E.; Kennedy, Martin J.; Rice, Dennis; Allen, Michael F.
Abstract : Nilpenia rossi new genus new species, described here from the Ediacara Member (Rawnsley Quartzite, South Australia), provides evidence of a Precambrian macroscopic sessile sediment-dweller. Nilpenia, ranging up to 30 cm in diameter, consists of two zones, a complex central area surrounded by radiating, dichotomously branching structures that decrease in diameter from the center to the outer edges. Other elements of the Ediacara Biota are interpreted to have been mat-encrusters but Nilpenia uniquely grew within the upper millimeters of the actual sediment displacing sediment with growth. This sediment surface was rippled and cohesive and may well have included an endobenthic mat. The branching network on the upper surface of the organisms would have been in contact with the water. The phylogenetic relationships of the Ediacara biota are not well constrained and Nilpenia is no exception. However, the morphology and ecology of Nilpenia represent a novel growth strategy present in the Ediacaran and not common today.